FACTOR INFLUENCING ON PREVENTIVE BEHAVIORS OF RESPIRATORY TRACT INFECTIONS AMONG CAREGIVERS OF PRESCHOOL AGED CHILDREN IN CHILDCARE CENTER, BANGKOK METROPOLITAN ADMINISTRATION - Laemthaisong, Jaruwan; Toonsiri, Chanandchidadussadee; Homsin, Pornnapa (Journal of Public Health Nursing, 2019)
Preventive behaviors of respiratory tract infections are important behavior that helps to control the communicable disease in childcare center. The purpose of this research was to identify factors influencing on preventive behaviors of respiratory tract infections among caregivers of preschool aged children in childcare center. A cluster random sampling method was used to recruit the sample of 157 caregivers of preschool aged children in childcare center. Research instruments were included. a demographic data, knowledge, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, perceived self-efficacy, received information, and preventive behaviors of respiratory infected diseases questionnaires. Reliability 74, .70, .82, .85, .72, .88 .90. Data was analyzed by using descriptive statistics and the Stepwise multiple regression analysis. The results revealed that the sample had mean scores of preventive behaviors of respiratory infected diseases at good level (M = 60.20, SD = 4.37). The highest average score was primary care (M = 3.91, SD = .28). The significant predictors of preventive behaviors of respiratory infected diseases were knowledge, age, and perceived barriers. The model explained 12.5 % of variance (R2 = .125, p < .05). Results of the study suggested that nurse could apply this programs to promote preventive behaviors of respiratory infected diseases. focus on knowledge and perceived barriers.